PENGEMBANGAN EDUPRENEURSHIP MELALUI KANTIN KEJUJURAN UNTUK PENGUATAN LITERASI KEWARGANEGARAAN DAN NUMERASI SISWA - Ati Aryani; Deni Zein Tarsidi; Joko Daryanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the role of implementing honesty canteens in shaping students’ character and numeracy skills through a Systematic Literature Review (SLR) approach. The review examines various studies discussing the effectiveness of honesty canteen programs as a medium for character education within school environments. Data were obtained from five articles identified through Google Scholar based on PRISMA criteria. The findings indicate that honesty canteens make a significant contribution to fostering students’ values of honesty, responsibility, discipline, and integrity through experiential learning. In addition to serving as a means of internalizing moral values, honesty canteens also have the potential to develop basic numeracy skills through transactional activities involving price calculation, payment, and change. However, the success of this program’s implementation depends on the support of school culture, teachers’ role modeling, and student participation. Overall, the honesty canteen represents a contextual, integrative, and relevant approach to character education aligned with the principles of 21st-century learning.